2018
DOI: 10.1051/matecconf/201816201020
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical properties of reinforced clayey soil using nylons carry’s bags by products

Abstract: All structures built on soft soil may experience uncontrollable settlement and critical bearing capacity. This may not meet the design requirements for the geotechnical engineer. Soil stabilization is the change of these undesirable properties in order to meet the requirements. Traditional methods of stabilizing or through in-situ ground improvement such as compaction or replacement technique is usually costly. Now a safe and economic disposal of industrial wastes and development of economically feasible groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As a consequence of the examination of the effects of fiber addition on the stress-strain behavior of soils classified as CL according to the unified soil classification system (Asadollahi and Dabiri, 2017;Salim et al, 2018;Prabakar and Siridihar, 2002;Al-Adili, 2012;Najjar et al, 2014;Ple and Le, 2012), it was observed that the UCS, cohesion and internal friction angle values of the soil with the addition of glass fiber with 10 mm length and the content of 0,8% by weight are increased approximately 33%, 33% and 24%, respectively. Moreover, with the addition of 6 mm length of 5% nylon fiber by volume, the undrained shear strength of the soil increased approximately 120%, and with the addition of 20 mm length of 0,75% sisal fiber by weight the undrained cohesion and internal friction angle values increased approximately 267% and 11%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of the examination of the effects of fiber addition on the stress-strain behavior of soils classified as CL according to the unified soil classification system (Asadollahi and Dabiri, 2017;Salim et al, 2018;Prabakar and Siridihar, 2002;Al-Adili, 2012;Najjar et al, 2014;Ple and Le, 2012), it was observed that the UCS, cohesion and internal friction angle values of the soil with the addition of glass fiber with 10 mm length and the content of 0,8% by weight are increased approximately 33%, 33% and 24%, respectively. Moreover, with the addition of 6 mm length of 5% nylon fiber by volume, the undrained shear strength of the soil increased approximately 120%, and with the addition of 20 mm length of 0,75% sisal fiber by weight the undrained cohesion and internal friction angle values increased approximately 267% and 11%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They explained that the initial stiffness of the cement-fiber-soil mixture was less than that of the cemented-soil and that the stiffness decreased with the increase of cement content in the cement-soil-fiber mixture. Salim et al (2018) used recycled nylon fibers obtained from waste nylon bags to stabilize a soft clay soil with low bearing capacity and high compressibility. They used fibers of 6 mm length at the content of 1-5%.…”
Section: Polyvinyl Alcohol Fiber (Pva)mentioning
confidence: 99%
See 1 more Smart Citation
“…In geotechnics, several techniques are used to improve soils. Stabilization is the method of mixing different soils or adding additives to soil to enhance soil characteristics such as strength, durability, gradation, and plasticity, which makes soils more stable [7]. The main purpose of soil mass reinforcement is to improve its stability to increase its bearing capacity, and to reduce settlements and lateral deformations [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods of soil reinforcement, such as: stone columns [10], root piles, soil nailing and reinforced earth. Reinforced earth is a composite material consisting of compacted backfill and artificial reinforcing materials such as fibrous materials (geosynthetic and randomly distributed fibers) [7].…”
Section: Introductionmentioning
confidence: 99%